ETIKA DAN KINERJA MAHASISWA (Jurnal Riset Akuntansi, 2022)
This study was conducted to determine and examine the influence between ethics and student performance. This study uses primary data through a questionnaire using quantitative methods. Respondents are accounting students who take management accounting courses at Widyatama University. The data analysis used is simple linear regression analysis and processed using the SPSS 20 application by setting a significance level of 0.05 for hypothesis testing. The results of the study show that there is an influence of the application of ethics variables (X1) and student performance (Y) on Accounting Students at Widyatama University, which is 0.731. Keywords: Ethics, student performance, Lecturer